Value relevance of fair value hierarchy - Salim, Mursalam (Jurnal Akuntansi dan Auditing Indonesia, 2024)
Implementing accounting standard 68 (PSAK 68) adopted by IFRS 13 has brought changes in reflecting the market value previously explained by earnings per share and book value. This study investigates the relevance of fair value estimates as measured by the beta coefficient in firms in the financial industry. Specifically, the study focuses on whether the hierarchy of fair value financial liabilities and assets of the firms can affect the market value. This is quantitative research using archival methods. Sampling used a purposive sampling technique with a sample of 240 firm-years. The results showed that financial assets for level 2 (inputs other than quoted prices that were observable directly or indirectly) and level 3 (unobservable inputs generated by entities) positively had value relevance. All three hierarchy fair values of financial liabilities fair value negatively had value-relevance. These results indicate that investors pay higher financial assets for levels 2 and 3 than level 1. Meanwhile, the value relevance of financial assets and liabilities, as measured by R-squared, was relevant. This suggests that investors also trust that each hierarchy's fair value affects the market value. The findings of this study have significant implications for the advancement of the clean surplus theory. The theory posits that the company's market value can be explained by the fair value of financial assets using level 2 and level 3 as well as level 1, level 2, and level 3 financial liabilities.